2((2m+3)-1(1-2m))=2(3(3+2m)-3(3-m))

Simple and best practice solution for 2((2m+3)-1(1-2m))=2(3(3+2m)-3(3-m)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2((2m+3)-1(1-2m))=2(3(3+2m)-3(3-m)) equation:


Simplifying
2((2m + 3) + -1(1 + -2m)) = 2(3(3 + 2m) + -3(3 + -1m))

Reorder the terms:
2((3 + 2m) + -1(1 + -2m)) = 2(3(3 + 2m) + -3(3 + -1m))

Remove parenthesis around (3 + 2m)
2(3 + 2m + -1(1 + -2m)) = 2(3(3 + 2m) + -3(3 + -1m))
2(3 + 2m + (1 * -1 + -2m * -1)) = 2(3(3 + 2m) + -3(3 + -1m))
2(3 + 2m + (-1 + 2m)) = 2(3(3 + 2m) + -3(3 + -1m))

Reorder the terms:
2(3 + -1 + 2m + 2m) = 2(3(3 + 2m) + -3(3 + -1m))

Combine like terms: 3 + -1 = 2
2(2 + 2m + 2m) = 2(3(3 + 2m) + -3(3 + -1m))

Combine like terms: 2m + 2m = 4m
2(2 + 4m) = 2(3(3 + 2m) + -3(3 + -1m))
(2 * 2 + 4m * 2) = 2(3(3 + 2m) + -3(3 + -1m))
(4 + 8m) = 2(3(3 + 2m) + -3(3 + -1m))
4 + 8m = 2((3 * 3 + 2m * 3) + -3(3 + -1m))
4 + 8m = 2((9 + 6m) + -3(3 + -1m))
4 + 8m = 2(9 + 6m + (3 * -3 + -1m * -3))
4 + 8m = 2(9 + 6m + (-9 + 3m))

Reorder the terms:
4 + 8m = 2(9 + -9 + 6m + 3m)

Combine like terms: 9 + -9 = 0
4 + 8m = 2(0 + 6m + 3m)
4 + 8m = 2(6m + 3m)

Combine like terms: 6m + 3m = 9m
4 + 8m = 2(9m)

Remove parenthesis around (9m)
4 + 8m = 2 * 9m

Multiply 2 * 9
4 + 8m = 18m

Solving
4 + 8m = 18m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-18m' to each side of the equation.
4 + 8m + -18m = 18m + -18m

Combine like terms: 8m + -18m = -10m
4 + -10m = 18m + -18m

Combine like terms: 18m + -18m = 0
4 + -10m = 0

Add '-4' to each side of the equation.
4 + -4 + -10m = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -10m = 0 + -4
-10m = 0 + -4

Combine like terms: 0 + -4 = -4
-10m = -4

Divide each side by '-10'.
m = 0.4

Simplifying
m = 0.4

See similar equations:

| 4x^2+12x-14=0 | | 72b^2=4 | | 90=x*18 | | 4m+2b=28 | | 2a-5whena=7 | | 30+d=30+d | | 1/3h-4(2/3h-3)=2/3-3 | | -x*-x+2x*2x=11.33 | | log(7)x-log(7)(x-1)=1 | | 2.67(18)+x(6)=3 | | 4(x-5)=11(x+2) | | 5m+2n=10 | | -16=x/7 | | (3xy)^2/y^2= | | 4x+(5x+4)=134 | | (3xy)^2/y^2 | | -2/9=7/x | | 1.7(2)=n | | 12x^2-40x+144=0 | | 3j+2k=14 | | 12k+7=13 | | 12k+7=14 | | -9=x/-19 | | 6-(3)n=39 | | 3(1-4c)=25.5 | | 1/12=x/30 | | 2j+k=6j-k=8 | | 5p+4(2t)=364 | | 10+4(m+7)= | | 73+48+54+48=180 | | 6-3n=39 | | 43a+10-26=27 |

Equations solver categories